PENGARUH LATIHAN UPHILL SPEED RUN TERHADAP KECEPATAN LARI PEMAIN SEPAK BOLA SSB REMAJA KLUB KECAMATAN PANTI - Syahirus Syafiq; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of Uphill Speed Run Trainingon the Running Speed of Teenager SSB Soccer Players in the Panti District Club. Thestudy was conducted in the SSB Youth Club field, Panti District, Pasaman Regency,West Sumatra, conducted in March-September 2019. The sampling technique to be usedis full sampling / total sampling, which is determining the sample if all members of thepopulation are used as a sample. This is done if the total population is relatively small,less than 30 people or research that wants to make generalizations with very smallerrors, so the sample of this study is 12 people. From the data analysis and discussion,it can be concluded that there is an effect of Uphill speed run training on the speed ofthe SSB Youth Club Teen Club Panti District as evidenced by the results of tcount of14,241> ttable 1,796 at α = 0.05. This proves that by doing Uphill speed run exercises,the speed can be better results. From the analysis it can also be concluded that there isan effect of the Uphill speed run exercise on increasing speed. Programmed andcontinuous training, the more routine we do Uphill speed run training, the better theteam speed will be.Key Words: Uphill Speed Run Training, Running Speed